Imagens: arte e cultura [Images: art and culture], organized by Alexandre Santos and Ana Maria Albani de Carvalho - Dalcol, Francisco (PORTO ARTE: Revista de Artes Visuais, 2018)
Organization by Alexandre Santos and Ana Maria Albani de Carvalho, the book "Imagens: arte e cultura (Images: art and culture) (Editora da UFRGS, 2012, 336 pages) gathers 19 articles and essays that investigate the relations between image and culture in the spheres of history, theory and criticism. The texts present studies from researchers who share interest in the reflection on the mechanical image – especially the photographic one, from its emergence in the 19th century to the present – and the later practices of image production, such as the cinema, the video and the digital. The book has as important contribution the establishment of interchanges between different approaches and research methodologies related to the phenomenon of the image.